A comprehensive review of various approaches for treatment of tertiary wastewater with emerging contaminants: what do we know? - Zahmatkesh, Sasan; Bokhari, Awais; Karimian, Melika; Zahra, Musaddak Maher Abdul; Sillanpää, Mika; Panchal, Hitesh; Alrubaie, Ali Jawad; Rezakhani, Yousof (Environmental monitoring and assessment, 2022)
In the last few decades, environmental contaminants (ECs) have been introduced into the environment at an alarming rate. There is a risk to human health and aquatic ecosystems from trace levels of emerging contaminants, including hospital wastewater (HPWW), cosmetics, personal care products, endocrine system disruptors, and their transformation products. Despite the fact that these pollutants have been introduced or detected relatively recently, information about their characteristics, actions, and impacts is limited, as are the technologies to eliminate them efficiently. A wastewater recycling system is capable of providing irrigation water for crops and municipal sewage treatment, so removing ECs before wastewater reuse is essential. Water treatment processes containing advanced ions of biotic origin and ECs of biotic origin are highly recommended for contaminants. This study introduces the fundamentals of the treatment of tertiary wastewater, including membranes, filtration, UV (ultraviolet) irradiation, ozonation, chlorination, advanced oxidation processes, activated carbon (AC), and algae. Next, a detailed description of recent developments and innovations in each component of the emerging contaminant removal process is provided.
Keywords: Humans; Chlorination; Sewage; Ecosystem; Endocrine Disruptors; Environmental Monitoring; Ozone; Emerging contaminants; Ozonation; lidé; ozon; čištění vody; Wastewater; monitorování životního prostředí; endokrinní disruptory; Waste Water; Water Purification; UV irradiation; odpadní vody; Cosmetics; Water Pollutants, Chemical; Advanced wastewater treatment; kosmetické přípravky; Activated carbon; Advanced oxidation process; odpadní voda; Membrane; Charcoal; dřevěné a živočišné uhlí; chemické látky znečišťující vodu; ekosystém